Continent ileostomy with ileostomy bag. Kock technique. - Carriquiry, Luis A; Lapiedra, Eduardo; Lapiedra, Eduardo; Piñeyro, Alberto; Beltrán, Ricardo; Gutiérrez Galiana, Horacio; Pradines, Jorge C (Cirugía del Uruguay, 1985)
The authors present the first clinical observations carried out in our country in which, alter total proctocholectomy in two stages, a continent ileostomy was practiced using Kock's technique, with good results. Description of the technique employed, facilitated by the use of mechanical suture instruments and postoperative treatment.